Salinity variation of south-western coastal region of Bangladesh in response to discharge from an upstream river - Shibly Anwar, Md .; Zakir Hasan, Md.; Rahman, Kalimur (International Journal of Advanced Geosciences, 2020)
Long term variation in upstream water flow through the Ganges−Gorai river are affecting the salinity levels of south-western coastal region of Bangladesh. Salinity data for the Rupsha river was collected for several years to demonstrate the historical changes of salinity level in the south-western coastal region. Furthermore, discharge data of the Ganges and Gorai river were also collected to discuss the effect of upstream discharge on the variation of salinity level. This study also collected water and soil samples from different places of this region to measure the salinity level and compare the values with the standard ones. A decreasing trend in dry season Ganges-Gorai river flow was observed after the initiation of the Farakka barrage in 1975. Consequently, the south-western region underwent high salinity level. The Ganges sharing treaty in 1996 and dredging of the Gorai riverbed (GRRP-I and GRRP-II) in 1999 and in 2012 helped the region to recover from high salinity level for a certain period. The salinity level of the collected water samples was in alarming level but soil sample was not in so frightening condition in 2015. Results suggested that to maintain the salinity level of south-western region within the acceptable limit for drinking, fisheries, and cultivation purposes, approximately 80 m3/s Gorai river discharges required at dry season. To do that, it is necessary to ensure 1200 m3/s discharge through the Ganges river at the Hardinge Bridge point. To protect the vital south-western region, it becomes necessary to optimize flow augmentation in the Ganges-Gorai river and to continue the further phases of restoration project in the future.